Surface States and Photoluminescence From Porous Silicon - Md. Nazrul Islam; Satyendra Kumar (Журнал нано- та електронної фізики)
Photoluminescence (PL) spectra of freshly electrochemically etched porous silicon layers anodized under various condition have been measured and analyzed according to quantum confinement (QC) model and surface state models. The results support the combination of QC and surface state models for visible PL from fresh PS layers.